Enhanced Production Of Nitrate Reductase By Lactic Acid Bacteria For The Synthesize Of Silver Nanoparticles - Loi, Hsean Ren (2023)
Among the emerging nanotechnology, silver nanoparticles (AgNPs) get much attention due to their unique physicochemical. The present study aimed to optimize nitrate reductase production in lactic acid bacteria (LAB) for enhanced production of AgNPs. LAB isolates were screened for nitrate reduction ability and their activities were quantified using nitrate reductase enzyme assay. Lactobacillus plantarum CAM 4 was selected for the optimization of nitrate reductase activity due to highest nitrate reductase activity measured among LAB isolates.